2021
DOI: 10.18235/0003379
|View full text |Cite
|
Sign up to set email alerts
|

Impacto del COVID-19 en la demanda de energía eléctrica en Latinoamérica y el Caribe

Abstract: En esta monografía, se presenta un análisis del impacto de la pandemia en términos de demanda eléctrica comparándolo con un modelo de un año habitual para cada uno de los países seleccionados. Esto permitió identificar primero cuánta electricidad se dejó de demandar y por ende de cobrar en la pandemia; cuáles fueron las alteraciones a este consumo; y cuál es el camino hacia la recuperación. Este documento establece cuál es el impacto de la pandemia con respeto a un año estándar modelado específico para cada p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…also reconfigured in terms of duration and usage. In a similar study covering ten countries in the LAC region (including Bolivia), Sánchez Ubeda et al (2021) found that the COVID pandemic and associated economic measures led to a sharp overall decrease of energy demand (from all economic sectors, including households). The largest monthly energy consumption drop compared to historical energy use trends was registered in Peru (-32%) and Bolivia (-26.7%) in April 2020.…”
Section: Emergency Policy Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…also reconfigured in terms of duration and usage. In a similar study covering ten countries in the LAC region (including Bolivia), Sánchez Ubeda et al (2021) found that the COVID pandemic and associated economic measures led to a sharp overall decrease of energy demand (from all economic sectors, including households). The largest monthly energy consumption drop compared to historical energy use trends was registered in Peru (-32%) and Bolivia (-26.7%) in April 2020.…”
Section: Emergency Policy Responsesmentioning
confidence: 96%
“…A parsimonious set of plausible values for s and functional forms for f were empirically explored for each city to identify the model specification that provided the best fit. External predictors included different lags of energy consumption, and variables coming from external sources, supported by existing literature (see e.g., Qarnain et al, 2020;Sánchez Ubeda et al, 2021). These were: monthly temperature in each city, a data point sourced from the National Service of Hydrology and Meteorology in Bolivia (SENAMHI) 5 , and the NIS Global Index of Economic Activity (IGAE, in Spanish), which measures the monthly level of economic activity in each city 6 .…”
mentioning
confidence: 99%
“…O ano de 2020 foi excluído da análise devido a pandemia de COVID-19 (WB, 2021;WHO, 2021), que causou forte variação e declínio na produção e consumo de energia dos países (Beljansky et al, 2020;Ubierna, Alberti and Alarcón, 2020;BP, 2021;Sánchez Úbeda et al, 2021). Portanto, a fonte hídrica disponível para à IET-AS são os 𝑅𝐸𝑆 𝐻𝑒𝑥𝑝𝑙 da Bolívia, Colômbia, Peru, Suriname, Venezuela e as UGs binacionais 71 possíveis de serem implantadas com o Brasil.…”
Section: Ambos Osunclassified